2018
DOI: 10.1093/ndt/gfy071
|View full text |Cite
|
Sign up to set email alerts
|

Low thyroid function is not associated with an accelerated deterioration in renal function

Abstract: Low thyroid function is not associated with a deterioration of renal function. The cross-sectional association may be explained by renal dysfunction causing thyroid hormone alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
(78 reference statements)
2
27
0
1
Order By: Relevance
“…Previous studies have shown that the decline in eGFR can be reversed, or at least attenuated, by exogenous thyroid hormone replacement, which indicates that kidney dysfunction could be the end result of functional changes rather than histological damage [7,8]. While a recent large study showed, that there is an association between LFT and renal function deterioration and proteinuria [5], other large sample size studies either failed to demonstrated such association [11] or found opposite result [9]. These discrepancies could be explained by the design of the study (longitudinal vs. cross-sectional) and population enrolled (general vs. CKD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the decline in eGFR can be reversed, or at least attenuated, by exogenous thyroid hormone replacement, which indicates that kidney dysfunction could be the end result of functional changes rather than histological damage [7,8]. While a recent large study showed, that there is an association between LFT and renal function deterioration and proteinuria [5], other large sample size studies either failed to demonstrated such association [11] or found opposite result [9]. These discrepancies could be explained by the design of the study (longitudinal vs. cross-sectional) and population enrolled (general vs. CKD).…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort, in patient with normal kidney function, Zhan Y et al found an increased incidence of CKD in patients with hypothyroidism after a median follow-up of 3.5 years [10]. In contrast, Mewese CL et al [11], examining 72,856 individuals with overt hypothyroidism, subclinical hypothyroidism, and euthyroidism, concluded that low thyroid function was not associated with faster decline of renal function.…”
Section: Introductionmentioning
confidence: 98%
“…Secondly, kidney dysfunction may predispose to thyroid hormone changes, via influence on the metabolism of thyroid hormones or due to chronic illness (as CKD) leading to nonthyroidal illness as potential underlying pathophysiological mechanisms (23,26). A recent individual participant data analysis from 16 independent cohorts of the Thyroid Studies Collaboration found no role for thyroid hormones in kidney dysfunction (15). However, it does not exclude that previously found crosssectional associations between kidney and thyroid (10, 11) may be explained by kidney dysfunction causing thyroid hormone changes.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have presented conflicting results, linking kidney function decline to low (13) or high thyroid function (14). Whereas a recent individual participant data analysis found no role for thyroid hormones in renal function decline, it does not exclude reverse causality, indicating that previously found cross-sectional associations between kidney and thyroid may be explained by kidney dysfunction causing thyroid hormone changes (15). Whether or not kidney function causally alters thyroid hormones, several studies have shown an increased prevalence of subclinical thyroid disease and nonthyroidal illness in patients with CKD (16,17), and this may be associated with higher mortality (18).…”
Section: Introductionmentioning
confidence: 89%
“…Current research suggests that the correlation between hypothyroidism and renal function still remains unclear. A meta-analysis of individual patient data showed that, although decreased thyroid function was shown to correlate with lower eGFR values when evaluated cross-sectionally, there was no association between SCH and deterioration of renal function over time [ 35 ]. On the other hand, another recent study evaluating over 15,000 patients found an association between pre-ESRD TSH levels and post-ESRD mortality, with a higher risk of mortality observed among patients with incrementally higher TSH levels [ 36 ].…”
Section: Discussionmentioning
confidence: 99%